Video educativo para fomentar la práctica del karate-do, en jóvenes en situación de vulnerabilidad. - Ontaneda Rubio, Dayana Yasmin (Quito; 2013, 2013)
Through an investigative process, we have reached the conclusion that Karate-Do is a martial sport that allows people to develop values, not only inside the Dojo, but outside in their daily lives. However, Karate-Do is not a massively spread sport. That’s the reason why, through methodological application, we have developed a series of diffusion proposals. A theoretical contribution has been proposed in the methodological framework; this is an investigation that will turn into feasible and practical alternatives to solve media difficulties. This feasible proposal has been defined as an educational video to stimulate the practice of Karate-Do in young people who are in a vulnerable situation.